To achieve total irrigation, Nitish Kumar must subsidise water pumps, not electricity - Kishore, Avinash (Foundation for Independent Journalism, 2020)
The state must also combine the provision of irrigation with public procurement of rice and wheat and improved access to markets for high-value crops.